Corporate-Community Engagement as a part of CSR best practice: case study of Malaysian Palm Oil Multinational Companies in Indonesia - Siti Amaliya Mohd Radyi (2020)
Over the past three decades, Corporate Social Responsibility (CSR) has steadily emerged as one of the most critical plans for the business community, locally and internationally. Therefore, achieving this agenda requires corporations to look beyond monetary profit. One of the integral components of CSR is through Corporate-Community Engagement (CCE), which identified as a viable means for the sustainability of the palm oil industry. Specifically, this study explores CCE as practised by Malaysian Palm Oil Multinational Companies (MPOMC) in Indonesia. Despite the fact that the Indonesian government has regulated CSR as a mandatory act, they do not specify the CSR measurement in detail, so that generally, it is not considered crucial among the Indonesian companies. Additionally, since Malaysia and Indonesia contribute to approximately 90% of total world production of palm oil, they are the leaders in the industry and the palm oil industry itself has undoubtedly become the engine of economic growth in the said countries. Nevertheless, the rapid growth of this industry leads to severe environmental and social issues, especially the social-ecological issue that has been highly debated over the last three decades. Hence, the palm oil industry is considered as the most appropriate case for the study. This study aims to examine the CCE concept’s practices from the community context and to deeply understand the way MPOMC organizes CCE internationally. It also investigates the anatomy of stakeholder dynamics in five case studies of Malaysian multinational companies that operate in Indonesia. A total of 30 semi-structured in-depth interviews are conducted with the locals, employees, and government officers. This study was carried out in five different MPOMCs, from three different provinces in Indonesia: Sumatera, Kalimantan and Aceh. In order to answer the broad question, this study investigates the approaches of CSR engagement process practised by the target groups in the host country and reveals stakeholder’s perception on this concept as well as shows the factors that influence companies to practice the CCE process. Therefore, the results of this study conclude with the CCE model that could help the palm oil companies in maintaining a good relationship and collaboration with the communities for both socio-economic developments of the locals as well as the sustainability of the industry. Based on the investigation done, the approaches in the CCE model are interconnected with each other. It is crucial for the approaches to be undertaken and organised well by the companies, so that there is equality in terms of development in rural areas and the sustainability of the industry.